Suicidal Ideation among Individuals with Borderline and Narcissistic Trends: A cross-cultural study of Chinese and Pakistani adolescents and young adults - Tariq Ahmed,; Xing Qiang,; Mudassar Abdullah, (Al-Qanṭara, 2024)
Suicide is a major public health problem, among adolescents and young adults. In this study, we aimed to examine the relationship between the traits of Borderline personality disorder (BPD), narcissistic personality disorder (NPD), and suicidal ideation and behaviors. Adolescents and young adults mean age of 23.6 (SD = 6.1) were screened with standardized questionnaires 1, Scale for Suicidal Ideation (SSI-19), 2, Borderline Personality Inventory (BPI-53), and 3, Narcissistic Personality Inventory (NPI-16) assessing suicidal ideation, traits of Borderline personality disorder and Narcissistic personality disorder. Descriptive statistics, parametric tests, Pearson correlation coefficients, and reliability analysis were utilized for differences in the population mean scores. Pakistanis have a significantly lower mean score of 5.1 than Chinese (mean score of 6.9) on NPI-16 (t = -7.22, p < 0.001), indicating a substantial difference between the two populations. Similarly, Pakistani participants have a lower mean score of 4.2 than Chinese participants' mean score of 7.6 on BPI-53 with inverse significant differences (t = -15.61, p < 0.001), and large effect size (d = 1.02). However, Pakistanis have a significantly lower mean score (5.5) than the Chinese mean score of 7.7 for suicidal ideation with an inverse statistically significant difference (t = -5.25, p < 0.001) and a modest effect size (d = 0.37). These findings emphasize the importance of considering cultural context when interpreting psychological assessments and designing interventions aimed at addressing suicidality and mental health issues. Keywords: Suicide, Suicidality, Borderline Personality Disorder, Narcissistic Personality Disorder and Psychological assessment